Adenoma and colorectal cancer risks in Lynch syndrome, Lynch‐like syndrome and familial colorectal cancer type X. Issue 1 (14th September 2021) - Bucksch, Karolin; Zachariae, Silke; Ahadova, Aysel; Aretz, Stefan; Büttner, Reinhard; Görgens, Heike; Holinski‐Feder, Elke; Hüneburg, Robert; Kloor, Matthias; von Knebel Doeberitz, Magnus; Ladigan‐Badura, Swetlana; Moeslein, Gabriela; et al.
Abstract: Lynch syndrome (LS), Lynch‐like syndrome (LLS) and familial colorectal cancer type X (FCCX) are different entities of familial cancer predisposition leading to an increased risk of colorectal cancer (CRC). The aim of this prospective study was to characterise and to compare the risks for adenoma and CRC in these three risk groups. Data was taken from the registry of the German Consortium for Familial Intestinal Cancer. Patients were prospectively followed up in an intensified colonoscopic surveillance programme that included annual examinations. Cumulative risks for adenoma and CRC were calculated separately for LS, LLS and FCCX, and then for males and females. Multivariate Cox regression was used to analyse the independent contributions of risk group, mismatch repair gene (within LS), sex and previous adenoma. The study population comprised 1448 individuals (103 FCCX, 481 LLS and 864 LS). The risks were similar for colorectal adenomas, but different for first and metachronous CRC between the three risk groups. CRC risk was highest in LS, followed by LLS and lowest in FCCX. Male sex and a prevalent adenoma in the index colonoscopy were associated with a higher risk for incident adenoma and CRC. In patients with LS, CRC risks were particularly higher in female MSH2 than MLH1 carriers. Our study may support the development of risk‐adapted surveillance policies in LS, LLS and FCCX. Abstract : What's new? While associations between colorectal cancer (CRC) risk and Lynch syndrome (LS) are well‐described, less is known about CRC risks linked to the closely related Lynch‐like syndrome (LLS) and familial colorectal cancer type X (FCCX). In this prospective follow‐up study of patients with LS, LLS, and FCCX, risks were similar for colorectal adenomas but considerably different for first and metachronous CRCs. In addition, LS females who carried MSH2 mutations had notably higher CRC risks than female MLH1 mutation carriers. The identification of variations in carcinogenic pathways between LS, LLS, and FCCX could enable risk‐adapted CRC surveillance for these syndromes.